The Impact of Emotional Labor on User Stickiness in the Context of Livestreaming Service—Evidence From China - Shi, Yunxia; Ma, Chunhao; Zhu, Yuxin (Frontiers in Psychology, 2021)
Improving the user stickiness become increasingly valued, due to urgent problem of user churn of live streaming services. Previous studies pay much attention to technology factors on user stickiness, ignoring the emotional factors on user stickiness. This study examined the impact of network anchors’ emotional labor (deep acting vs. surface acting) on user stickiness in the live streaming service context. We extended prior findings in three ways. The results of Study 1 (questionnaire method, 305 live streaming users, 56.4% female) demonstrated that emotional labor of network anchor positively influenced user stickiness, and immersion experience plays a mediating role. The results of Study 2 (situational simulated method, 203 volunteers, 54.09% female) demonstrated that deep acting strategies of emotional labor had a stronger effect compared to surface acting strategies. The results of Study 3 (situational simulated method, 235 volunteers, 51.9% female) demonstrated that the effect of emotional labor on user stickiness was stronger for the users with prevention focus compared to promotion focus. These results highlight the role of emotional labor in improving user stickiness, and suggest that platform should value the training for network anchor and the analysis of user characteristics.